Mapping Temperature Distribution Generated by Photothermal Conversion in Graphene Film Using Er,Yb:NaYF4 Nanoparticles Prepared by Microwave-Assisted Solvothermal Method - Savchuk, Oleksandr A.; Carvajal, Joan J.; Cesteros, Yolanda; Salagre, Pilar; Nguyen, Huu Dat; Rodenas, Airan; Massons, Jaume; Aguiló, Magdalena; Díaz, Franscesc (Frontiers in Chemistry, 2019)
We report the mapping of temperature distribution generated by graphene in a glass slide cover after illumination at 808 nm with a good thermal resolution.. For that, Er,Yb:NaYF4 nanoparticles prepared by a microwave-assisted solvothermal method were used as upconversion luminescent nanothermometers. By tuning the basic parameters of the synthesis procedure, such as the time and temperature of reaction and the concentration of ethanol and water, the size and the crystalline phase of the nanoparticles could be controlled, getting the right conditions to obtain 100 % of the  hexagonal phase, the most efficient spectroscopically. We observed that the thermal sensitivity that can be achieved with these particles is a function of the size of the nanoparticles and the crystalline phase in which they crystallize. We believe that, with the suitable changes, these nanoparticles might be used to map temperature gradients in living cells in the future maintaining a good thermal resolution.